Digestion system for destruction of organic matter in food analyses - Sakuma, Alice Momoyo; Oliveira, Jorge José do Vale; Zenebon, Odair; Tiglea, Paulo; Scorsafava, Maria Anita (Instituto Adolfo Lutz Journal - RIAL, 1989)
It is proposed a simple system to destroy organic matter by wet digestion. Several kinds of foods were tested and the results showed that this method i s more efficient and faster than the conventional methods used for ashing organic matter in order to evaluate metallic contaminants in foods.